Diversity and Community Composition of Large Wading Birds Across Three Contrasting Wetlands of Kollam, Kerala - Sreelal, R. S.; Vijayan, Reshmi; Hegde, Maitreyi (Asian Journal of Biological and Life Sciences, 2026)
Background: Wetlands along the southwest coast of India support diverse assemblages of large wading birds, many of which serve as ecologic indicators. Materials and Methods: This study assessed the diversity, abundance, and seasonal distribution of large wading birds across three wetlands in Kollam district, Kerala - Polachira wetland, Munroethuruthu backwaters, and Ashtamudi Lake. Monthly surveys using point counts were conducted between December 2024 and May 2025. Diversity was evaluated using Shannon–Wiener Index (H′) and Simpson’s Diversity Index (1-D). Species richness and species assemblage patterns were assessed using a Bray– Curtis dissimilarity matrix and NonMetric Multidimensional Scaling. Results and Discussion: A total of 12 species were recorded from Polachira, six species from Munroethuruthu, and five species from Ashtamudi Lake. Polachira exhibited the highest diversity (H′ = 2.19, 1-D = .87), while Ashtamudi Lake showed significantly lower diversity (H′ = 1.09, 1-D = .55). One species Asian Woollyneck Ciconia episcopus was Near Threatened, which was recorded only in Polachira. Seasonal peaks were observed during January and February, with a decline in May, in all three wetlands. NonMetric Multidimensional Scaling and beta diversity indexes showed a clear distinction of species assemblages in Polachira, compared to the other two sites. Conclusion: The study highlights Polachira as an important habitat for large wading birds in southern Kerala, and disturbance regulation in Ashtamudi Lake despite its Ramsar status. Regular monitoring of wading-bird assemblages is recommended as a bioindicator tool for wetland conservation planning.
Keywords: Bioindicators; Kerala; Near Threatened species; Ramsar site; Wading birds; Wetland; conservation